2023
DOI: 10.1038/s41598-023-41837-4
|View full text |Cite
|
Sign up to set email alerts
|

Tmem161a regulates bone formation and bone strength through the P38 MAPK pathway

Takuya Nagai,
Tomohisa Sekimoto,
Syuji Kurogi
et al.

Abstract: Bone remodeling is an extraordinarily complex process involving a variety of factors, such as genetic, metabolic, and environmental components. Although genetic factors play a particularly important role, many have not been identified. In this study, we investigated the role of transmembrane 161a (Tmem161a) in bone structure and function using wild-type (WT) and Tmem161a-depleted (Tmem161aGT/GT) mice. Mice femurs were examined by histological, morphological, and bone strength analyses. Osteoblast differentiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…p38 MAPK signaling pathway is essential for bone formation and bone strength in vivo. 52 , 53 The p38 MAPK pathway also plays a central role in the regulation of monocyte/macrophage development and differentiation. 54 57 To validate the mechanism of Tim4-regulated CD301b + macrophages phenotype, we focused on p38 MAPK signaling pathway because evidences have described that Tim4 in macrophages could mediate p38 MAPK signaling pathway and might facilitate tissue regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…p38 MAPK signaling pathway is essential for bone formation and bone strength in vivo. 52 , 53 The p38 MAPK pathway also plays a central role in the regulation of monocyte/macrophage development and differentiation. 54 57 To validate the mechanism of Tim4-regulated CD301b + macrophages phenotype, we focused on p38 MAPK signaling pathway because evidences have described that Tim4 in macrophages could mediate p38 MAPK signaling pathway and might facilitate tissue regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…The overexpression of StTMEM161A leads to reduced levels of oxidant-induced DNA damage and apoptosis. Previous study indicated that TMEM161A plays a role in protecting against oxidative stress [57]. This gene is activated by calcium as a chloride channel.…”
Section: Wgcna Analysis For Pvy Resistancementioning
confidence: 99%
“…The sections were deparaffinized with toluene and rehydrated using a graded ethanol series, and then autoclaved at 120C for 15 min in 10-mM citrate buffer (pH 6.0). 19,20 After inhibition of endogenous peroxidase activity with 3% H 2 O 2 in methanol for 30 min, the sections were preincubated with 500-µg/ml normal goat IgG and 1% BSA in PBS for 1 hr to block nonspecific binding of antibodies. The sections were then reacted with the following primary antibodies for 16-17 hr: anti-HMGB2 (cat.…”
Section: Animals and Tissue Preparationmentioning
confidence: 99%